Carbon solubility in Cu-based composite prepared by mechanical alloying - 冉旭 刘勇兵 包晓军 刘学然 安健 (Transactions of Nonferrous Metals Society of China, 2006)
The powder mixture of Cu and graphite was mechanically alloyed （MA） in an oscillating type ball mill. The milling time was varied in order to investigate its influence on the microstructural evolution of mechanically alloyed powders. The phase constituent, alloying characteristics, grain size and lattice distortion of these powders were determined by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy and transmission electron microscopy. The results show that the C is confirmed to dissolve in the Cu lattice, forming solid solution of carbon in copper the lattice parameter of copper increases with carbon concentration increasing, up to a saturation value of about 4%C（mass fraction）. Higher ball-mill energy is beneficial for twins and nanograin formation.